Prospects of Artificial Kefir Grains Prepared by Cheese and Encapsulated Vectors to Mimic Natural Kefir Grains - Xue Han; Huaxi Yi; Sainan Zhao; Jialei Sun; Yu Wang (Journal of Food Quality)
Kefir is a natural fermented dairy beverage obtained by fermenting milk with kefir starter grains. However, up to now, there is still no efficient approach to producing stable kefir grains by using the pure or cultural mixture of strains isolated from the original kefir grains. Therefore, new techniques need to be taken to promote the kefir grain production. To this purpose, an encapsulated vector produced by entrapment of the dominant strains isolated from kefir grain and the cheese vector which was produced by a traditional manufacturing method was used to mimic kefir grain forming, respectively. Then, the composition, microstructure, and microflora of the two vectors were investigated and were compared with the natural kefir grains. Results indicated that the protein and polysaccharide content of cheese vector were much higher than encapsulated vector; the distribution of microorganisms inside the cheese vector was more similar to that inside the natural kefirs. It indicated that the cheese vector would be more suitable to mimic kefir grain production. Results of the present investigations reveal the potential of the cheese vector for kefir grains production at the industrial level.